CFE and military stability in Europe - Peters, John E. (RAND, 1997)
RAND's research effort to provide analytic support over the past two years to the Office of Non-Nuclear Arms Control, Office of the Under Secretary of Defense for Policy, has ranged widely. First, it aided preparation for the CFE (Conventional Forces in Europe) Implementation Review Conference held in May 1996 and, more recently, reinforced U.S. negotiations in the CFE Adaptation Talks. Over the ensuing months, the project has explored U.S. negotiating options and the consequences associated with potential new foreign arms control proposals. This report is a record of our analytic support. The report describes the main activities and involvements of the project. It features two principal chapters, one dealing with the big questions about the future of CFE and one that describes more-technical details and modeling of arms control pacts. A final chapter suggests what can be learned from the past two years of arms control support and offers some brief recommendations for the United States' conventional arms control agenda. The author counsels in this report against undertaking additional pan-European conventional arms control initiatives. To the extent that arms control will be useful in the near future, it will involve more-local agreements tailored specifically to address grievances among neighbors. Unless circumstances alter dramatically, Europe-wide negotiations will make little sense, especially in the face of NATO enlargement, for which, presumably, allies will not negotiate arms control pacts with each other.